MANAGING THE TEACHING COMPETENCE OF PART-TIME INSTRUCTORS AT ILOCOS SUR POLYTECHNIC STATE COLLEGE, PHILIPPINES - Leonard Manuel; Maria Teresa Garcia; Jessie James Sangalang (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
There is little investigation on the exposure of non-education part-time instructors to pedagogical experience in higher education and on practical support and opportunities for their professional development. This study examined the non-education part-time instructors’ level of competence in teaching tasks through the quantitative approach employing the descriptive-correlative design. The result showed that although there was a high competence in instructional preparation among the non-education part-time instructors, it found that there was moderate competence in constructing learning outcomes and in integrating them with learning activities. Similarly, the respondents also acquired a high level of competence in instructional delivery but showed a lower rating in the appropriate application of teaching methods during instruction. Although a very high competence in psychosocial support was recorded, results showed that their level of competence in assessment and feedback was high. Still, they were found moderately competent in employing various assessment techniques. In correlating these variables with the respondents’ profiles, the four areas of teaching tasks were significantly associated with formal training, and educational attainment was significantly correlated to instructional delivery. It concluded that there is a need to provide a support mechanism through the adoption of the expanded program for non-education part-time instructors.